Polacy o Włochach – Włosi o Polakach. Język, literatura, kultura - Mazurkiewicz, Adam; Lenartowicz Zagrodna, Anna; Wismont, Magdalena; Berkan Jabłońska, Maria; Kołodziej, Karolina (Wydawnictwo Uniwersytetu Łódzkiego, 2026)
The monograph is composed of three parts devoted respectively to language, literature, and culture, all examined within the context of Polish–Italian relations. The linguistically oriented section includes lectures devoted to lexis (Polish–Italian lexical borrowings over the centuries, Italian vocabulary in Polish culinary terminology), paremiology (linguistic and semantic similarities and differences), and the history of the Polish language. A separate paper addresses Latin–Polish linguistic contacts. Latin not only gave rise to the Romance languages but also served as the first language of the Polish elite. The section concludes with an analysis of three travel reports by Henryk Sienkiewicz from his journey to Italy. The literary section comprises studies devoted, respectively, to Polish–Italian literary relations from the sixteenth to the eighteenth centuries and to the influence exerted by the works of Giambattista Marino on Polish Baroque authors in terms of poetics, stylistics, and thematic scope. Subsequent papers explore the impact of Italian literature and culture on the generation of Polish Romantics and post-Romantics. One study focuses on ekphrastic poems by selected Polish poets. The literary section concludes with a lecture presenting the figure and work of Stanisław Lem. The section on culture opens with a paper devoted to Hetman Jan Zamoyski, followed by a study discussing Polish–Italian relations on the dynastic, diplomatic, and political levels, showing how these contacts contributed to the incorporation of cultural and social elements in both Poland and Italy. The monograph concludes with a lecture presenting the five Polish laureates of the Nobel Prize in Literature and outlining the reception of their works in Italy.